Kata Bahasa Indonesia Penanda Register Twitter: Suatu Kajian Morfologi - Rima Rismaya; Wahya Wahya; Fahmy Lukman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study was conducted to describe the formation and meaning of Indonesian words as Indonesian Twitter's tweet register markers. This research is a qualitative descriptive study with data collection methods using listen and note method. The referential equivalent method and the content analysis method with the presentation of the results of data analysis carried out using formal and informal methods are two methods used in data analysis. The data source is Twitter user comments in the six tweets of the @areajulid account with the most comments in 2021. The results show that there are five ways of forming Indonesian words as Twitter registers, namely the process of (1) affixation, including the words "mengjamet", "mengkesal", and "membagongkan"; (2) abbreviations include the words "mjb", "pen", "jamet", "lontang", "sat", "dahlah", and "monmaap"; (3) anagrams include the words "kane", "isilop", and "ngab"; (4) hybrids include the words "kenawhy", "akhlakn't", and "jujurly"; and (5) changes in the form of syllables in basic words including the words "anjir", "anjrit", "santuy", "gemoy", and "cangtip". The purposes of using the Indonesian word Twitter register marker are (1) to express feelings; (2) to make fun of; (3) to greet; and (4) to misspelt words.